The Integration of Advanced Drug Delivery Systems into Conventional Adjuvant Therapies for Peri-Implantitis Treatment - Iria Seoane-Viaño; Mariola Seoane-Gigirey; Carlos Bendicho-Lavilla; Luz M. Gigirey; Francisco J. Otero-Espinar; Santiago Seoane-Trigo (MDPI AG, 2024)
Despite the high success rates of dental implants, peri-implantitis is currently the most common complication in dental implantology. Peri-implantitis has an inflammatory nature, it is associated with the accumulation of plaque in the peri-implant tissues, and its evolution can be progressive depending on various factors, comorbidities, and poor oral health. Prophylaxis and different treatment methods have been widely discussed in recent decades, and surgical and non-surgical techniques present both advantages and disadvantages. In this work, a literature review of different studies on the application of adjuvant treatments, such as local and systemic antibiotics and antiseptic treatments, was conducted. Positive outcomes have been found in the short (up to one year after treatment) and long term (up to ten years after treatment) with combined therapies. However, there is still a need to explore new therapies based on the use of advanced drug delivery systems for the effective treatment of peri-implantitis in the long term and without relapses. Hence, micro- and nanoparticles, implants, and injectable hydrogels, among others, should be considered in future peri-implantitis treatment with the aim of enhancing overall therapy outcomes.